Prime editing strategies to mediate exon skipping in DMD gene - Happi Mbakam, Cedric; Roustant, Jeanne; Rousseau, Joel; Yameogo, Pouire; Lu, Yaoyao; Bigot, Anne; Mamchaoui, Kamel; Mouly, Vincent; Lamothe, Gabriel; Tremblay, Jacques P. (Frontiers in Medicine, 2023)
Duchenne muscular dystrophy is a rare and lethal hereditary disease responsible for progressive muscle wasting due to mutations in the DMD gene. We used the CRISPR-Cas9 Prime editing technology to develop different strategies to correct frameshift mutations in DMD gene carrying the deletion of exon 52 or exons 45 to 52. With optimized epegRNAs, we were able to induce the specific substitution of the GT nucleotides of the splice donor site of exon 53 in up to 32% of HEK293T cells and 28% of patient myoblasts. We also achieved up to 44% and 29% deletion of the G nucleotide of the GT splice site of exon 53, as well as inserted 17% and 5.5% GGG between the GT splice donor site of exon 51 in HEK293T cells and human myoblasts, respectively. The modification of the splice donor site for exon 51 and exon 53 provoke their skipping and allowed exon 50 to connect to exon 53 and allowed exon 44 to connect to exon 54, respectively. These corrections restored the expression of dystrophin as demonstrated by western blot. Thus, Prime editing was used to induce specific substitutions, insertions and deletions in the splice donor sites for exons 51 and 53 to correct the frameshift mutations in DMD gene carrying deletions of exon 52 and exons 45 to 52, respectively.